ALK gene aberrations and the JUN/JUNB/PDGFR axis in metastatic NSCLC. Issue 9 (3rd April 2014) - Berghoff, Anna Sophie; Birner, Peter; Streubel, Berthold; Kenner, Lukas; Preusser, Matthias
<x xml:space="preserve">Abstract</x> Anaplastic lymphoma kinase (ALK) gene aberrations are found in several tumor types including anaplastic large cell lymphoma (ALCL) and non‐small cell lung cancer (NSCLC). Crizotinib, an inhibitor of ALK‐fusion proteins, has shown clinical activity, but resistance mechanisms limit long‐lasting disease control. It has been shown that ALK‐NPM fusion upregulates platelet‐derived growth factor receptor beta (PDGFRB) via JUN and transcription factor Jun B (JUNB) in ALCL. PDGFRB inhibition has been identified as therapy option for ALK‐positive ALCL. Here, we investigated the ALK/JUN/JUNB/transcription factor Jun C (JUNC)/PDGFR axis in metastatic NSCLC with regard to ALK aberrations. We performed immunohistochemical analysis of platelet‐derived growth factor receptor alpha (PDGFRA), PDGFRB, JUNB and JUNC expression in formalin‐fixed, paraffin‐embedded specimens of 15 NSCLC brain metastases (5 ALK translocations, 3 of them involving EML4, 5 ALK amplifications, 5 without ALK aberrations). We did not find a statistically significant difference in expression of PDGFRA, PDGFRB, JUNB or JUNC in tumor samples with normal ALK status, ALK amplification or ALK translocations (Kruskal–Wallis test p > 0.05). Interestingly, PDGFRB was not expressed in tumor cells (but in vascular and stromal cells) in any of our cases. Our data argue against PDGFRB activation in association with ALK gene aberrations in metastatic NSCLC and thus seem to imply differential pathobiological roles of ALK alterations in lung cancer and lymphoma, possibly depending on different fusion partner genes. These results may be relevant for targeted therapies, as they indicate that inhibition of PDGFRB in ALK translocated NSCLC seems to be no therapeutic opportunity.